Differentiated Instruction in English Language Class at UPT SMP 1 PANGSID - Sofiah; Andi Asrifan; Nadirah; Sam Hermansyah; Isumarni (International Journal of Global Sustainable Research, 2024)
This study used descriptive qualitative method as the research methodology. Data collection procedures used questionnaires and interviews. The population in this study were English students at UPT SMP 1 PANGSID school with a sample of 29 students of class VIII2. The existing data will be analyzed by describing the percentage results of the diagram and then given a conclusion as the final result.  The findings of this study indicate that differentiated learning strategies can improve student learning outcomes. With the differentiated learning strategy, respondents can choose a learning style that is suitable for the learning interests of each student. Differentiated learning strategy also has a positive role in increasing students learning motivation.